MORPHOFUNCTIONAL CHANGES IN THE SMALL INTESTINE IN CHILDREN WITH PNEUMONIA (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Pneumonia remains one of the leading causes of childhood mortality. Respiratory system damage activates systemic response reactions in the organism and negatively affects distant organs, including the morphofunctional state of the small intestine. This article analyzes structural and functional changes occurring in the small intestinal mucosa in children with pneumonia, including villous atrophy, enterocyte damage, microcirculatory disorders, and pathogenetic mechanisms of inflammatory processes. The study demonstrates the systemic effect of pneumonia on the gastrointestinal tract, substantiating the necessity of a comprehensive approach in pediatric practice.